Pneumocysterol [ (24Z) - ethylidenelanost - 8 - en -3 rare sterol detected in opportunistic pathogen Pneumocyctis carinii hominis : Structural identity and chemical synthesis - Kaneshiro, E.S; Amit, Z.; Swonger, M.M; Kreishman, G.P; Brooks, E.E; Kreishman, M.; Jayasimhulu, K.; Sun, H.; Kizito, S.A; Beach, D.H; Parish, E.J (Proc. Natl. Acad. Sci. USA, 1999)
Edna S. Kaneshiro, Zunika Amit, Mardie M. Swonger, George P. Kreishman, Elwood E. Brooks, Mara Kreishman, Koka Jayasimhulu, Hang Sun, Stephen A. Kizito, David H. Beach, Edward J. Parish.